DAMPAK PEMBANGUNAN INFRASTRUKTUR JALAN TERHADAP PENINGKATAN EKONOMI MASYARAKAT DESA BASARANG - Pamungkur . Pamungkur (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the current state of rural road infrastructure and its impact on local economic growth, as well as identifies key challenges and opportunities for enhancing road networks to support sustainable rural development. Using a qualitative approach, this research seeks to understand the economic impact of road construction on village communities. Data was collected through in-depth interviews with community members, local business owners, and village authorities to capture the economic and social changes following road development. Thematic analysis was applied to reveal community perceptions regarding the benefits of road infrastructure in Basarang village, located in Basarang District. The road construction in Montong Ajan successfully improved accessibility and supported local economic activity, evident in higher agricultural commodity prices, easier distribution of agricultural products, and reduced transportation costs. The project has also fostered the growth of small and medium enterprises in the village due to improved access. Despite remaining challenges, such as the need for additional infrastructure, the positive impacts of this project are expected to continue with ongoing maintenance support from the village administration. In the future, community participation in infrastructure maintenance is anticipated to help sustain these long-term benefits.